Chewable Tablets: A Comprehensive Review - Swapnil Sandip Shingade,; Trushali A. Mandhare,; Pooja S. Kashid,; Otari, Kishor (Asian Journal of Pharmaceutical Research and Development, 2024)
Tablets that can be chewed between the teeth must be broken before consumption. These tablets are provided to individuals who like swallowing and to youngsters who have difficulty swallowing. These tablets are designed to dissolve smoothly and quickly in the mouth, either with or without chewing. Typically, chewable tablets have a smooth texture when they dissolve, have a fruity flavour, and leave no bitter or unpleasant taste. Tablets that can be chewed between the teeth must be broken before consumption. These tablets are provided to individuals who like swallowing and to youngsters who have difficulty swallowing. These tablets are designed to dissolve smoothly and quickly in the mouth, either with or without chewing. Typically, chewable tablets have a smooth texture when they dissolve, have a fruity Flavour, and leave no bitter or unpleasant taste. Tablets that can be chewed between the teeth must be broken before consumption. These tablets are provided to individuals who like swallowing and to youngsters who have difficulty swallowing. These tablets are designed to dissolve smoothly and quickly in the mouth, either with or without chewing. Typically, chewable tablets have a smooth texture when they dissolve, have a fruity flavour, and leave no bitter or unpleasant taste.